Relation of the subject of financial investigations with other branches of knowledge - Лепський, Станіслав Іванович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
This article analyzes the scientific point of view about the place, role, content and subject matter of financial investigations, among other disciplines. Several specific aspects of financial investigations: economic, legal, forensic, criminological and psychological. Indicated that financial investigation is inappropriate to restrict illegal expropriation of property, the subject may include a financial component and other crimes.